Seamless Transitions: From Teacher to Substitute and Back Again. (20th January 2021) - Stoddart, Alexandra L.; Cameron, Nicole
Abstract : This article provides best practices for both teachers and substitute teachers; not only will these suggestions help teachers and substitutes, but they will also help ease the transition for students and maximize learning while their teacher is away. Practical examples of strategies for teachers are included such as phonetically spelled class lists and concise substitute folders with need to know and nice to know information to be communicated to the substitute. Advice for substitutes to transition the teaching space back to the teacher is also included.